Imbalance of the interleukin 1 system in colonic mucosa—association with intestinal inflammation and interleukin 1 receptor agonist genotype 2. Issue 5 (1st November 1997) - Andus, T; Daig, R; Vogl, D; Aschenbrenner, E; Lock, G; Hollerbach, S; Köllinger, M; Schölmerich, J; Gross, V
Abstract : Background— Interleukin 1 (IL-1) α and β are potent cytokines which play key roles in inflammation. They are controlled by IL-1 receptor antagonist (IL-1ra). Aims— To investigate the influence of mucosal inflammation and IL-1ra genotype on the IL-1ra:IL-1 balance. Patients and methods— IL-1α, IL-1β, and IL-1ra were measured by enzyme linked immunosorbent assay (ELISA) in biopsy specimens taken from inflamed and non-inflamed colon of 60 patients with Crohn's disease (CD), 34 with ulcerative colitis (UC), 15 inflammatory controls, and 103 non-inflamed controls. IL-1ra genotype was determined by polymerase chain reaction and gel electrophoresis. Results— IL-1α and IL-1β were significantly increased in inflamed mucosa in inflammatory bowel disease (IBD) (CD: 53.5 (22.4) and 409.9 (118.7) pg/mg protein, respectively; UC: 18.9 (6.8) and 214.5 (78.2) pg/mg, respectively) and non-IBD patients (19.2 (7.4) and 281.4 (121.0) pg/mg, respectively; p<0.0001) compared with normal controls (2.8 (0.6) and 30.6 (5.6) pg/mg, respectively). In CD IL-1α and β were also significantly increased in non-inflamed mucosa (6.1 (1.3) pg/mg and 88.7 (17.4) pg/mg, respectively; p<0.0012). IL-1ra:(IL-1α+β) ratios were significantly decreased in inflamed mucosa of patients with CD (182 (45); p<0.0001), UC (425 (136); p=0.0018) and without IBD (221 (76); p<0.0001), and in non-inflamed mucosa in CD (369 (149); p<0.0001) compared with normal controls (1307 (245); p<0.0001). Patients with IL-1ra genotype 2 had slightly but significantly reduced mucosal IL-1ra concentrations (p=0.003). The greatest difference was seen in colonic biopsy specimens from patients with inflamed Crohn's disease. Conclusion— Mucosal inflammation can modulate the balance of the IL-1:IL-1ra system in colonic mucosa.